Poland China swine - Garver, James R. (My University, 1907)
Introduction: Fossil forms of the genus Sus have been found as early as the middle of the Pliocene to the middle of the Miocene time. Our first traces of the real Pecarries come in the Oligocene and Eocene time. The groupe reached an important stage of its evolution in the Tertiary Period, and to the present time this family has made many changes and variations. In connection with the Geological origin of this family we should also consider its original habitat and disposition that we may the better see wherein the improvements have been made and also that we may understand what characteristics this family has had which has made it so important and useful.
Citation: Garver, James R. Poland China swine. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Fossils; Peccaries; Geologic Time Periods; Theses